Xenotransplantation Procedure and its Potential Effect on Man - Bisong, Peter (Advances in Social Sciences Research Journal, 2015)
Xenotransplantation is not yet a clinical procedure, such that one can just work into a clinic and demand for it to be carried on him/her. However, considering the energy and enthusiasm with which researches on xenotransplantation are carried out, it is reasonable to think that in the near future, it will become a clinical success. There are already series of debate as to the potential benefits of xenotransplantation – would it introduce a world plague to humans or would it provide a better life for them. This is a heated debate. This paper joins in this debate and avers that xenotransplantation should be halted, for it is better to halt actions when one is in doubt. Since the safety of xenotransplantation is in doubt, research on it need to be suspended, until we are certain that it is risk free.